Creole seeds what do we think about them? A study on the perception of Family farmers of the municipality of Saudade do Iguaçu/PR - Telles, Carolini dos Santos; Godoy, Cristiane Maria Tonetto; Oliveira, Paulo Henrique de; Vargas, Thiago de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2018)
In the current scenario loss of genetic variability is a serious problem, due to the current production model that recommends the use of genetically modified and hybrid seeds. In this sense, there are proposals for sustainable agricultural systems and production, one of the existing strategies to guarantee the food and environmental security of the populations is the use of creole seeds, opposing conventional production. The present article aims to address the perception of family farmers in the municipality of Saudade do Iguaçu, Paraná, in relation to the use and importance of creole seeds in the production of properties. To achieve this goal, the semi-structured interview technique was used with 26 family farmers. The results show that there are some cultivars of creole seeds in the rural properties, mainly the beans Creole. However, the farmers’ perception of these seeds is still linked to the notion of low productivity, believing that commercial seeds are the best, allied to the application of agrochemicals. In this sense, it is important to demystify this perception created by the modernization of agriculture, so that sustainable rural development can be achieved.